Hubungan Antara Penyesuaian Diri Dan Harga Diri Dengan Subjective Well Being - Al-Karimah, Nur Fadhilah; , Dr. Taufik Kasturi, M.Si (2015)
The aims of this research are to prove empirically: 1) relationship between self adjustment with the increasing of subjective well being in people with disability; 2) relationship between self-esteem with the increasing of subjective well being in people with disability; 3) relationship between self adjustment and self-esteem with the increasing of subjective well being in people with disability. The subjects of this research are students with disability in BBRSBD Prof. Dr. Soeharso, Surakarta, Central Java about 140 students. Data collection method used self adjustment scale, self-esteem scale and subjective well being scale. The method of analysis data used multiple regression analysis. The result of data analysis suggests that there is a significant relationship between self adjustment and self-esteem with subjective well being in students with disability. The aspect of self adjustment variable has the most dominant influence towards subjective well being more than self esteem, while the least influenced aspect is self-esteem aspect. Implications for psychological science education that is the subject of the evaluation as well as the necessary role of psychology to increase subjective well being in people with disability.